Nikah Mut’ah dalam Sorotan Hukum Islam dan Hukum Positif - A. Dzarrin al-Hamidi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2008)
In Islam, marriage lasts until death does the couple apart. Nonetheless, if one or both parties cannot fulfill the rights and perform the duties of marriage, a marriage can end up in divorce. Likewise, if a marriage ends with the death of one of the two parties, the surviving spouse is allowed to remarry. The above description about the essence of marriage cannot be found in temporary marriages. In temporary marriages, a marriage is set to last for a certain time without obligation of providing support and all kinds necessary for normal marriages such as housing, medicines, clothes, and so on. Pregnancy is also part of the contract. Likewise, no inheritance is resulted from such marriages. There is also no divorce as well as right for just treatment in case of the husband is polygamous. The only right for wife is dowry. Thus, there is no responsibility in contemporary marriages. Those marriages are only a means for fulfillment of biological needs whenever a man and a woman have to be in a place away from family for certain period of time.